Increasing Enteral Protein Intake in Critically Ill Trauma and Surgical Patients. (7th February 2019) - O'Keefe, Grant E.; Shelton, Marilyn; Qiu, Qian; Araujo‐Lino, Jose Cruz
Abstract: Background: Published guidelines recommend providing at least 2 g/kg/d of protein for critically ill surgical patients. It may be difficult to achieve this level of intake using standard enteral formulas, thus necessitating protein or amino acid supplementation. Herein, we report our approach to enteral protein supplementation and its relationship with urinary nitrogen excretion and serum transthyretin concentrations. Methods: This was a retrospective cohort study in which we reviewed critically ill trauma and surgical patients treated with supplemental enteral protein according to a protocol aiming to deliver a total of 2 g/kg/d of protein. We collected detailed nutrition data over a 2‐week period after admission and obtained additional data through discharge to determine caloric and protein intake as well as complications. We also compared urine nitrogen excretion and transthyretin concentrations between these patients and a control group who did not receive supplemental protein. Results: Fifty‐three subjects received early protein supplementation. Formula and protein supplement each provided ≈1.2 g/kg/d of protein by intensive care unit day 4. This resulted in a median total protein intake of 2.2 g/kg/d through day 14. One patient developed acute kidney injury, and 1 patient had 3 episodes of vomiting. By the third week, serum transthyretin concentrations increased to a median of 21 mg/dL compared with 13 mg/dL in subjects not receiving early supplementation. Conclusion: It is safe to deliver supplemental protein enterally to critically ill surgical and trauma patients and reach 2 g/kg/d of protein intake during the first week of illness.